The role of the unsaturation degree on the droplet combustion characteristics of fatty acid methyl ester - Ibrahim Ahmad Ibadurrohman (Elsevier, 2022)
Biodiesel is composed of various types of methyl ester compounds with different concentrations. The role of unsaturation degree was observed through single-molecule droplet combustion from three fatty acid methyl ester compounds. This research was conducted under normal gravity at ambient temperature and atmospheric pressure. Analysis of droplet combustion characteristics was observed along the heating, evaporation, ignition, and combustion stages. The cis configuration and allyl groups in unsaturated molecules related to different unsaturation degrees affect the droplet combustion process. Allyl and bis-allyl groups play an important role in accelerating hydrogen atom abstraction due to the weaker bond dissociation energy of the CH bond adjacent to the carbon double bond. The lower energy gap in unsaturated molecules is prone to electron excitation. Increasing the unsaturation degree resulted in shorter ignition delay and burning duration but higher droplet temperature, burning rate constant, specific power output, and flame dimensions. Soot particles formed above the flame tip on the unsaturated molecules gave a higher flame dimension. A high concentration of linoleic methyl ester in biodiesel fuel is recommended due to of high power output. However, the soot formation at a higher level of unsaturation degree should be considered.